Kajian intensitas komitmen generasi ketiga pada perusahaan bisnis keluarga di Jakarta - Bernadine; Brastoro (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Family business has an important role in reinforcing the world economy. It is supportedby data that 80 % -98 % of business in the world is family business. Results of previousstudies showed empirical fact that only 12 % of family businesses were able to survive thethird generation and only 3 % are capable of growing up to the fourth generation . Thisstudy aims to assess the intensity of the commitment to the company's third generation ofthe family . By using purposive sampling technique was found 56 samples from the studypopulation of 106 students in business management class family in Kwik Kian Gie Schoolof Business odd semester 2013-2014. The data analysis of this study employed a qualitativeapproach using a likert scale and the mean score dimensional. This study concluded thatthe third generation has a strong commitment to the family business on a willingness,pride, involvement , and loyalty dimensions, while the next generation 's commitment invalues dimension are not as strong as the commitment of the other four dimensions.